Bone metastasis of limb segments: Is mesometastasis another poor prognostic factor of cancer patients?. (21st February 2020) - Tani, Shoichiro; Morizaki, Yutaka; Uehara, Kosuke; Sawada, Ryoko; Kobayashi, Hiroshi; Shinoda, Yusuke; Kawano, Hirotaka; Tanaka, Sakae
Abstract: Objective: In contrast to acrometastasis, defined as bone metastasis to the hand or foot, the frequency and prognosis of bone metastasis of other limb segments remain unclear. To compare prognosis according to sites of bone metastasis, we defined two new terms in this study: 'mesometastasis' and 'rhizometastasis' as bone metastasis of 'forearm or lower leg' and 'arm or thigh', respectively. Methods: A total of 539 patients who were registered to the bone metastasis database of The University of Tokyo Hospital from April 2012 to May 2016 were retrospectively surveyed. All patients who were diagnosed to have bone metastases in our hospital are registered to the database. Patients were categorized into four groups according to the most distal site of bone metastases: 'acrometastasis', 'mesometastasis', 'rhizometastasis' and 'body trunk metastasis'. Results: The frequency of rhizometastasis (22.5%) or body trunk metastasis (73.1%) was significantly higher than that of acrometastasis (2.0%) or mesometastasis (2.4%). The median survival time after diagnosis of bone metastases for each group was as follows: 6.5 months in acrometastasis, 4.0 months in mesometastasis, 16 months in rhizometastasis, 17 months in body trunk metastasis and 16 months overall. In survival curve, there was a statistically significant difference between mesometastasis and body trunk metastasis. Conclusions: Our findings suggest that 'mesometastasis' could be another poor prognostic factor in cancer patients and that patients with mesometastasis should receive appropriate treatments according to their expected prognosis. Abstract : We coined a new word mesometastasis: bone metastasis in the forearm or lower leg. Like acrometastasis, mesometastasis could be a poor prognostic factor in cancer patients.